A Review of the Observed Air Temperature in the Antarctic Peninsula. Did the Warming Trend Come Back After the Early 21st Hiatus? - Cordero-Carrasco, R (Elsevier B.V., 2021)
Recent changes in the near-surface air temperature (nSAT) in the Antarctic Peninsula (AP) suggests that the absence of 21st century warming on Antarctic Peninsula may be coming to end. To examine this, the long-term annual and seasonal variability of the nSAT at eight Antarctic stations located in the AP are analyzed using available data from the SCAR Reader database, complemented with data from the Chilean Weather Service (Frei and O Higgins). An exponential filter was applied to the original annual and seasonal mean series to obtain a decadal-like variation of the nSAT. A stacked and the standardized anomaly of the nSAT record was constructed to examine the average regional behavior in the AP. Cumulative sum (CUSUM) and changepoint analysis were applied through the stacked nSAT series to highlight significant changes caused by variation in weather and climate. The CUSUM and bootstrapping analysis revealed two statistically significant breaking points during the 1978–2020 period. The first one occurred in the late nineties ending a warming period and making the beginning of a cooling period; the second one may have taken place in the mid-2010s and could mark the end of the warming pause. These trends appear to be consistent with the changes observed in the large-scale climate modes (i.e., the Antarctic Annular Mode – AAO). © 2021 Elsevier B.V. and NIPR